Seasonal temperature variation in Zostera marina seedlings under ocean acidification - Wang, Zhaohua; Pei, Yanzhao; Yan, Wenjie; Lu, Lv; Zhou, Bin (Frontiers in Marine Science, 2023)
Objective To investigate the responses of Zostera marina seedlings to the individual and combined stresses of seasonal temperature increase and ocean acidification (OA) caused by global climate change and anthropogenic factors. This data will help in efforts to protect and restore seagrass beds in temperate coastal zones of China. Methods A mesoscale experimental system was utilized to analyze stress response mechanisms at multiple levels - phenotype, transcriptome, and metabolome - during the seedling stage of Z. marina, a dominant temperate seagrass species in China. The study monitored the seedlings under varying conditions: increased seasonal temperature, OA, and a combination of both. Results Findings revealed that under high-temperature conditions, carotenoid biosynthesis was stimulated through the upregulation of specific metabolites and enzymes. Similarly, the biosynthesis of certain alkaloids was promoted alongside modifications in starch, sucrose, and nitrogen metabolism, which improved the plant’s adaptation to OA. Unique metabolic pathways were activated under OA, including the degradation of certain amino acids and modifications in the citric acid cycle and pyruvate metabolism. When subjected to both temperature and OA stresses, seedlings actively mobilized various biosynthetic pathways to enhance adaptability and resilience, with distinct metabolic pathways enhancing the plant’s response under diversified stress conditions. In terms of growth, all treatment groups exhibited significant leaf length increase (p < 0.05), but the weakest growth index was observed under combined stress, followed by the thermal treatment group. Conversely, growth under OA treatment was better, showing a significant increase in wet weight, leaf length, and leaf width (p < 0.05). Conclusion Seasonal temperature increase was found to inhibit the growth of Z. marina seedlings to some extent, while OA facilitated their growth. However, the positive effects of OA did not mitigate the damage caused by increased seasonal temperature under combined stress due to seedlings’ sensitivity at this stage. Our findings elucidate differing plant coping strategies under varied stress conditions, contingent on the initial environment. This research anticipates providing significant data support for the adaptation of Z. marina seedlings to seasonal temperature fluctuations and global oceanic events like OA, propelling the effective conservation of seagrass beds.